P312 BSG survey on the impact of COVID-19 on workforce and wellbeing. (19th June 2022) - Kabir, Misha; Samji, Shairoz; Verma, Ajay; Matharoo, Manmeet; SWiG, BSG
Abstract : Introduction: Gastroenterology is a specialty at high risk of burnout, yet strategies are needed for workforce expansion to meet increasing service demands (BSG Workforce Report 2020). This survey aimed to evaluate the impact COVID-19 placed on workforce retention and wellbeing. Methods: A cross-sectional survey was distributed electronically to BSG physician members in August 2021. Responses were received over 6-weeks. Multivariable binary logistic regression and thematic qualitative analyses were performed. Results: Response rate : 8.8% (180/2044) of BSG physician members; 28.8% (180/624) of opened email invites 1) Consultants = 146 (80.6%); Trainees = 33 (18.4%) Aged 55+ years (27.8%) Female = 65 (36.1%); 9.2% (6/65) aged 55+ years Positive COVID-19 in 30.6% (55/180) 38.2% (21/55) felt pressured to return to work before ready Took > 1 month to return to pre-COVID health physically (35.1%) and mentally (38.4%) Shielding required by 10.1% (18/179) 94.4% (17/18) felt their workplace accommodated Regular increase in working patterns out of hours during pandemic in 43.8% (71/162) Due to staff shortages, more general medicine responsibilities, service backlog, administrative burden. Independently associated with new Consultants, minority ethnic background, or considering early retirement Service pressures: 91.5% (150/164) believe workforce inadequate to manage pandemic service backlog Consideration of own department's ability to deal with backlog: median score 77 (IQR 60-90) on Likert scale of 0 (not anxious at all) to 100 (highly anxious) Wellbeing: 49.1% (80/163) felt isolated from department due to remote working 65.9% (108/164) felt reduced face to face patient contact made job less fulfilling 73.9% (105/142) accessed/made aware of wellbeing resources Respondents suggested BSG could address burnout concerns by advocating for: o Workforce expansion (eg increased national training numbers) o Workforce retention (eg mentorship, guidance on flexible working, phased retirement) Flexible working: 32.7% (53/162) believe pandemic increased opportunities 34.0% (55/162) plan to work more flexibly post-pandemic Pandemic leading to/planning early retirement in 51.0% (83/163) Independently associated with male gender, increased out of hours working, and isolation from department Conclusions: Acknowledging the limitation of self-selection bias, the findings make stark reading, highlighting the additional burden the pandemic has placed on work-life balance, wellbeing and service demands within Gastroenterology. Increased aspirations for early retirement and flexible working need to be addressed in future workforce planning.